Efektivitas Teams Game Tournament (TGT) Terhadap Hasil Belajar Matematika Di SD - Laili Rahmawati (Universitas Negeri Makassar, 2017)
The result of student's mathematics learning is low. This study aims to determine the tendency of mathematics learning outcomes using cooperative learning model type Teams Games Tournament (TGT) and using conventional learning. The method used in this research is kuantitatif with Quasi Experimental Design approach. Result of analysis by using t-test if sig value <0,05. From the t-test results obtained sig value = 0.002 which means 0.002 <0.05, then the hypothesis proposed accepted and significant. There is a significant difference in the learning outcomes of Mathematics between the lessons using cooperative learning models of teams games tournament type (TGT) and those using conventional learning. Judging from the results of the cooperative model of cooperative learning type of teams games tournament (TGT) is higher than the use of conventional learning.